La literatura ancestral y su incidencia en la lectura comprensiva en la Unidad Educativa “29 de septiembre”, San miguel de Pomachaca, Guamote, Chimborazo. - Sagñay Guacho, Francisco (2022)
ABSTRAC In boys and girls in the eighth grade of primary education, there are difficulties in decoding words, sentences, phrases, expressions, and messages, a poor vocabulary in understanding the meaning of words and understanding of texts, as well as in the interpretation and the recognition of the literal level of the contents programmed by the teacher. The objective of this research is to improve comprehensive reading by applying ancient literature such as: (stories, legends, myths, and poetry). The theme corresponds to ancestral literature and its impact on extensive reading in the "September 29" educational unit. It was not possible to apply the population and the sample as planned with 29 students and two teachers in the eighth year of basic education because they did not know the ancestral literature. I had to support myself with the older adults of the community of San Miguel de Pomachaca. They are the ones who know stories, legends, myths, and traditions orally, which are linked to improving extensive reading so that the reader develops the ability to understand and interpret what is read about the meaning of the content of a text, to use to build new texts, as well as assess and develop the skills of understanding and construction of knowledge as a means of communication. An active methodology was within the cognitive model and with the collaborative work of local adults in both Spanish and Kichwa languages. With the information obtained through structured interviews before and after implementating the "Ancestral literature methodological guide for reading comprehension," a non- experimental, applied, descriptive, qualitative, and field research was conducted using a deductive method. Among the techniques used were the interview and observation; the instruments were handled through cards and the structured base test. It was concluded with the application of methodological and didactic strategies that favor reading comprehension in Spanish and Kichwa in any context, taking advantage of bilingualism and overcoming reading comprehension problems; The applicability of the "Ancestral literature methodological guide for reading comprehension" is recommended, it is adapted for the educational institution of the place, educational institutions of the rural and urban sector of the bilingual and Hispanic jurisdiction where bilingual boys and girls predominate, with problems of linguistic interference in the expression, literacy, and comprehension presented in most of the students. Keywords: Ancestral literature, extensive reading, stories, myths, legends, poetry. Firmado electrónicamente por: MARCELA PATRICIA GONZALEZ ROBALINO Reviewed by: Mgs. Marcela González Robalino English Professor c.c. 0603017708